The presence of lymphovascular and perineural infiltration after neoadjuvant therapy and oesophagectomy identifies patients at high risk for recurrence - Lagarde, S M; Phillips, A W; Navidi, M; Disep, B; Immanuel, A; Griffin, S M (British journal of cancer, 2015)
Background: In patients treated for oesophageal cancer the importance of lymphovascular and perineural invasion (PNI) after neoadjuvant therapy has yet to be established. The aim of this study was to assess the incidence and prognostic significance of these factors in a consecutive series of patients with cancer of the oesophagus or gastro-oesophageal junction (GOJ) who underwent neoadjuvant therapy followed by oesophagectomy. Methods: Clinical and pathology results from patients with potentially curable adenocarcinoma, or squamous cell carcinoma of the oesophagus or GOJ were reviewed. Patients were treated with neoadjuvant chemotherapy or chemoradiation followed by transthoracic oesophagectomy and two-field lymphadenectomy. The presence of venous invasion (VI), lymph vessel invasion (LI) and perineural invasion (PNI) were correlated with clinical outcomes. Results: A total of 396 patients underwent oesophagectomy after neoadjuvant therapy for oesophageal cancer. Venous invasion was identified in 150 (38%) of patients, LI in 203 (51%) patients and PNI in 204 (52%) patients. In all, 123 (31%) patients had no evidence of either VI, LI or PNI. A total of 96 (24%) had a combination of two factors and 94 (24%) had all three factors. The presence of VI, LI and PNI was significantly related to tumour stage ( P =0.001). Median overall survival was 170.8 months when all three factors were absent, 44.0 months when one factor was present, 27.1 months when two factors were present and 16.0 months when all were present. Multivariate analyses revealed VI, LI and PNI or a combination of these factors were independent predictors of prognosis. Conclusions: In oesophageal cancer patients treated with neoadjuvant therapy followed by oesophagectomy the presence of VI, LI and PNI has an important prognostic impact and may identify patients at high risk of recurrence who would benefit from adjuvant therapies.